Effectiveness of soil cover in controlling soil erosion in oil palm plantation / Efron Amung - Efron Amung (Faculty of Plantation and Agrotechnology, 2016)
Soil erosion has causes serious problem in damaging the soil productivity at oil palm plantation especially at hilly area. This research was conducted to find another alternative to control soil erosion instead using Legume Cover Crop (LCe) such as Mucuna braceata. The purpose of this research project is to determine the best soil cover practices in controlling soil erosion at hilly area on oil palm plantation. Three treatments were used for this project; Carpet grass (Axonopus compressus), plant residue and bare soil (control). Three criteria were tested to determine the most effective soil cover; firstly by measuring the amount of eroded sediment, secondly by determining the volume of runoff water and lastly by measuring the nutrients loss from soil eroded. The test was run with a 15 degree slope gradient stand-up apparatus by using watering can with four liter of water. Data of amount eroded sediment and volume runoff water were collected once the test was finished. The eroded sediment will then be brought to a laboratory for soil analysis and Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES) to determine the nutrient loss from the soil erosion. The research project results shows that, Carpet grass gave the lowest amount of eroded sediment with average mean 6.47 g, lowest volume of runoff water with average mean 1246.4 mL and less nutrients loss (phosphorus with average mean 611.22 mg/Kg and potassium with 48.27 mg/Kg) in soil compared to plant residue and bare soil. This result has proved that applying carpet grass as soil cover can help in reducing the soil erosion and nutrient loss. Therefore, it is recommended to use carpet grass for controlling soil erosion at hilly area.